تيسير النحو العربي: نقد ورؤية - حجازي، عبدالوهاب; دويس، محمد Duwais, Mohammed (المجلس الأعلى للغة العربية, 2019)
إن تيسير النحو فكرة قديمة جديدة، لكنها شاعت في العصر الحديث وبشدة نظرا لما يشتكيه أهل هذا العصر من صعوبة في تحصيله وعسر كبير في تعلمه، فحاول أهل العلم المحدثين الولوج في عملية بحث واسعة تشمل جميع الأطراف للخروج بحل فيصل لهذه الدعوة، واختلفت الرؤى من دارس لآخر وبكيفيات متنوعة وأساليب متباينة بحسب البيئة والفئة المستهدفة وغيرها.
The facilitation of grammar is a new old idea, but it has become common in the modern era and strongly because of what the people of this era complain of difficulty in learning and difficult to learn. Modern scholars tried to engage in a wide search process including all parties to come up with Faisal's solution to this call. For a variety of different methods and methods depending on the environment and the target, group and others.
Keywords: اللغة العربية -- النحو العربي -- تيسير النحو